2016
DOI: 10.1038/ncomms13053
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell lineage tracing in the mammary gland reveals stochastic clonal dispersion of stem/progenitor cell progeny

Abstract: The mammary gland undergoes cycles of growth and regeneration throughout reproductive life, a process that requires mammary stem cells (MaSCs). Whilst recent genetic fate-mapping studies using lineage-specific promoters have provided valuable insights into the mammary epithelial hierarchy, the true differentiation potential of adult MaSCs remains unclear. To address this, herein we utilize a stochastic genetic-labelling strategy to indelibly mark a single cell and its progeny in situ, combined with tissue clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
150
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(164 citation statements)
references
References 37 publications
10
150
0
Order By: Relevance
“…First, detailed analysis of mammary gland epithelium in whole‐mount stained for the basal or luminal cell markers, Keratin 14 and Keratin 8, respectively, allowed clones to be resolved by size and cell composition. From clonal maps showing both the representation of confetti labelled cells and their cell identity, it was apparent that, in line with similar clonal tracing studies (Davis et al., ; Lloyd‐Lewis, Davis, Harris, Hitchcock, & Watson, ; Van Keymeulen et al., ; Wuidart et al., ), by this stage of development, mammary stem cells have already become “compartmentalized”, lineage‐restricted to the basal or luminal compartments. However, based on these observations alone, further sublineage restriction within these compartments could not be ruled out.…”
Section: Unbiased Clonal Lineage Tracing Reveals the Multiplicity Andmentioning
confidence: 52%
“…First, detailed analysis of mammary gland epithelium in whole‐mount stained for the basal or luminal cell markers, Keratin 14 and Keratin 8, respectively, allowed clones to be resolved by size and cell composition. From clonal maps showing both the representation of confetti labelled cells and their cell identity, it was apparent that, in line with similar clonal tracing studies (Davis et al., ; Lloyd‐Lewis, Davis, Harris, Hitchcock, & Watson, ; Van Keymeulen et al., ; Wuidart et al., ), by this stage of development, mammary stem cells have already become “compartmentalized”, lineage‐restricted to the basal or luminal compartments. However, based on these observations alone, further sublineage restriction within these compartments could not be ruled out.…”
Section: Unbiased Clonal Lineage Tracing Reveals the Multiplicity Andmentioning
confidence: 52%
“…Three‐dimensional imaging combined with immunofluorescence staining for E‐cadherin would facilitate accurate quantification of the proportion of binucleated mammary epithelial cells within the rabbit mammary gland during pregnancy and lactation (Davis et al. ; Lloyd‐Lewis et al. ; Rios et al.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent quantitative analysis using saturation labeling with lineage markers strongly argues that these results were an artifact caused by promoter leakiness, and that all cells within the postnatal mammary gland arise solely from unipotent progenitors rather than multipotent stem cells 12 . Two additional recent studies used a different approach to generate stochastic genetic labelling and unbiased lineage-tracing methods that permanently label specific single clones, ultimately concluding that postnatal luminal and basal cells are lineage-restricted 13, 14 (Figure 1B). While several publications claim that these lineages arise from “unipotent stem cells”, we feel that this is a confusing term for what is really a progenitor, and that the term “stem cell” should be reserved for cells that exhibit multipotency.…”
Section: Mammary Epithelial Cells Have Limited Plasticity In Vivomentioning
confidence: 99%
“…However, a recent report showed that the enzymatic digestion method used to prepare mammary ducts for 3D imaging can deplete myoepithelial cells and cause structural damage to ducts, and potentially might also deplete rare bi-lineage clones 20 . New methods of micro-dissection or clearing, together with whole-organ 3D imaging analysis and mathematical modeling 8, 12, 13, 2123 , will undoubtedly provide a clearer picture of mammary gland cell fate during normal development.…”
Section: Mammary Epithelial Cells Have Limited Plasticity In Vivomentioning
confidence: 99%